Comparison of Orthodontic Treatment with Different Premolar Extraction Modalities İn Terms of Soft Tissue Profile - Tulin Taner; Ezgi Atik; Hande Gorucu-coskuner (Cumhuriyet University, 2019)
Objectives:To evaluate the differences of changes in soft tissue profile and dentoskeletal parameters between different premolar extraction and non-extraction treatment modalities. Materials and Methods: 50 patients with skeletal Class I malocclusion was divided into three groups. Group 1 consisted 17 patients (mean age:16.76±1.68 years) treated with maxillary and mandibular first premolar extractions; Group 2 consisted 16 patients (mean age:15.81±1.19 years) treated with maxillary and mandibular second premolar extractions, and Group 3 consisted 17 patients (mean age:16.29±1.15 years) treated with non-extraction protocol. From the pre-treatment (T0) and post-treatment (T1) cephalometric radiographs, 13 measurements for dentoskeletal and 15 for soft tissue parameters were assessed. To determine changes due to treatment, and to compare differences among the groups, Wilcoxon Signed-Rank and Kruskal-Wallis tests were performed, respectively.Results: Mx1-SN, Mx1-FH, Mx1-NA, IMPA and Md1-NB values decreased significantly in Group 1 and 2, compared to Group 3 (p<0.001). According to the vertical reference line (VRL-li) and E-plane (E-LL), the lower lip showed statistically significant change (retraction) in Group 1 and 2, compared to non-extraction group (p<0.05). The mean change value for the upper and lower lip thicknesses in Group 1 and 2 were greater than in Group 3 (p<0.05). Group 1 and 2 did not show significant difference in any dentoskeletal and soft tissue measurements between each other. Conclusions:Soft tissue profile change following extraction treatment was similar regardless of the extracted teeth. However extraction treatment modalities resulted in significant profile changes especially in the lower lip with regard to the non-extraction control group.